Atomic-Scale Simulations Confirm that Soluble β-Sheet-Rich Peptide Self-Assemblies Provide Amyloid Mimics Presenting Similar Conformational Properties - Yu, Xiang (The Biophysical Society, 2010)
The peptide self-assembly mimic (PSAM) from the outer surface protein A (OspA) can form highly stable but soluble β-rich self-assembly-like structures similar to those formed by native amyloid-forming peptides. However, unlike amyloids that predominantly form insoluble aggregates, PSAMs are highly water-soluble. Here, we characterize the conformations of these soluble β-sheet-rich assemblies. We simulate PSAMs with different-sized β-sheets in the presence and absence of end-capping proteins using all-atom explicit-solvent molecular dynamics, comparing the structural stability, conformational dynamics, and association force. Structural and free-energy comparisons among β-sheets with different numbers of layers and sequences indicate that in similarity to amyloids, the intersheet side chain-side chain interactions and hydrogen bonds combined with intrasheet salt bridges are the major driving forces in stabilizing the overall structural organization. A detailed structural analysis shows that in similarity to amyloid fibrils, all wild-type and mutated PSAM structures display twisted and bent β-sheets to some extent, implying that a twisted and bent β-sheet is a general motif of β-rich assemblies. Thus, our studies indicate that soluble β-sheet-rich peptide self-assemblies can provide good amyloid mimics, and as such confirm on the atomic scale that they are excellent systems for amyloid studies. These results provide further insight into the usefulness of such mimics for nanostructure design.